1988
DOI: 10.3186/jjphytopath.54.327
|View full text |Cite
|
Sign up to set email alerts
|

Host responses and nematode dispersion in Pinus strobus and P. densiflora infected with the pine wood nematode, Bursaphelenchus xylophilus.

Abstract: The pine wood nematode, Bursaphelenchus xylophilus (Steiner et Buhrer) Nickle, causes serious mortality of Japanese black pine, Pinus thunbergii Parl., and Japanese red pine, P. densi flora Sieb. et Zucc., in Japan. The inoculation test revealed that P. thunbergii and P. densiflora were susceptible to the infection of B. xylophilus, and some Pinus spp. including eastern white pine, P. strobus L., were resistant1,2). Pine wilt disease caused by B. xylophilus is characterized by rapid loss of xylem water con duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…5c). Similar results have been obtained by many researchers (Ikeda, 1996a;Ikeda and Kiyohara, 1995;Ikeda et al, 1994;Kuroda et al, 1991b;Odani et al, 1985b;Sasaki et al, 1984;Tamura et al, 1988). The cambium seemed to be degraded by cellulase activity of the virulent nematodes (Kusunoki, 1987).…”
Section: Physiological Changes In Stems 1 Physiological and Histologisupporting
confidence: 78%
See 1 more Smart Citation
“…5c). Similar results have been obtained by many researchers (Ikeda, 1996a;Ikeda and Kiyohara, 1995;Ikeda et al, 1994;Kuroda et al, 1991b;Odani et al, 1985b;Sasaki et al, 1984;Tamura et al, 1988). The cambium seemed to be degraded by cellulase activity of the virulent nematodes (Kusunoki, 1987).…”
Section: Physiological Changes In Stems 1 Physiological and Histologisupporting
confidence: 78%
“…However, symptom development of pine wilt disease is so rapid that many physiological changes appear at the same time. To avoid this problem, some researchers used resistant pine species and families to compare symptom development with susceptible ones (Ikeda et al, 1994;Kuroda et al, 1991b;Tamura et al, 1988;Yamada and Ito, 1993ab). Kiyohara (1989) and Kiyohara and Bolla (1990) reported a wide range of variation in the pathogenicity among pinewood nematode isolates, some of which never kilt pine trees.…”
mentioning
confidence: 99%
“…In both cases survival of the nematode is possible but, following transmission by feeding, the likelihood of spread of the nematode into the trunk of the tree depends on the susceptibility of the tree, infestation being restricted to the branches in native North American Pinus spp. (Wingfield & Blanchette, 1984;Bedker, 1987;Bedker et a[., 1987;Tamura et al, 1988). If the nematode is present in the trunk, it is capable of surviving and reproducing for at least one year and can thus be expected to be present on arrival in Europe.…”
Section: Roundwood With Barkmentioning
confidence: 99%
“…Nematode migration from inoculated branches to the top and base of trunks is very rapid comparable to that seen in P. thunbergii. TAMURA et al (1988) reported that larger numbers of B. xylophilus invaded the tissue of P. strobus than in susceptible P. densiflora. Following the primary distribution of nematodes, however, there was a clear decrease followed by slow increase in the size of the nematode population which differed from the continual increase seen in susceptible species.…”
Section: Jeeks After Neiatode Inoculationmentioning
confidence: 99%